Regeneration potential of decellularized periodontal ligament cell sheets combined with 15-deoxy-Δ12, 14-prostaglandin J2 nanoparticles in a rat periodontal defect. (2nd April 2021) - Jiang, Yao; Liu, Jia-Mei; Huang, Jia-Ping; Lu, Ke-Xi; Sun, Wei-Lian; Tan, Jing-Yi; Li, Bo-Xiu; Chen, Li-Li; Wu, Yan-Min
Abstract: Periodontitis is a chronic inflammatory disease characterized by loss of attachment and destruction of the periodontium. Decellularized sheet, as an advanced tissue regeneration engineering biomaterial, has been researched and applied in many fields, but its effects on periodontal regeneration remain unclear. In this study, the biological properties of decellularized human periodontal ligament cell (dHPDLC) sheets were evaluated in vitro . Polycaprolactone/gelatin (PCL/GE) nanofibers were fabricated as a carrier to enhance the mechanical strength of the dHPDLC sheet. 15-deoxy- Δ 12, 14 -prostaglandin J2 (15d-PGJ2 ) nanoparticles were added for anti-inflammation and regeneration improvement. For in vivo analysis, dHPDLC sheets combined with 15d-PGJ2 nanoparticles, with or without PCL/GE, were implanted into rat periodontal defects. The periodontal regeneration effects were identified by microcomputed tomography (micro-CT) and histological staining, and immunohistochemistry. The results revealed that DNA content was reduced by 96.6%. The hepatocyte growth factor, vascular endothelial growth factor, and basic fibroblast growth factor were preserved but reduced. The expressions or distribution of collagen I and fibronectin were similar in dHPDLC and nondecellularized cell sheets. The dHPDLC sheets maintained the intact structure of the extracellular matrix. It could be recellularized by allogeneic human periodontal stem ligament cells and retain osteoinductive potential. Newly formed bone, cementum, and PDL were observed in dHPDLC sheets combined with 15d-PGJ2 groups, with or without PCL/GE nanofibers, for four weeks post-operation in vivo . Bringing together all these points, this new construct of dHPDLC sheets can be a potential candidate for periodontal regeneration in an inflammatory environment of the oral cavity.